Galectin-1 Prevents Infection and Damage Induced by Trypanosoma cruzi on Cardiac Cells - Benatar, Alejandro Francisco (2015)
Fil: Benatar, Alejandro Francisco. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular (INGEBI). Laboratorio de Biología Molecular de la Enfermedad de Chagas (LabMECh); Argentina.